The significance of a complete internal audit data index in boosting an organization’s internal audit effectiveness - Abdul Aziz, Saliza; Raja Mohd Ali, Raja Haslinda; Sudin, Suhizaz; Rasit, Mohd Hadzrami Harun; Abdullah, Norkhairani (International Journal of Accounting, Finance and Business, 2025)
As business environments and regulatory landscapes become increasingly complex, strong internal audit functions are essential for ensuring effective governance, risk management, and compliance within organizations. Traditional auditing methods often fall short of addressing these challenges due to their limited scope and reactive tendencies. This paper investigates the creation and implementation of a comprehensive Internal Audit Data Index (IADI), a data-driven strategy designed to enhance the effectiveness of audits. The IADI unifies various data types, including financial, operational, compliance, and risk assessment information, into a cohesive framework. By harnessing advanced data analytics and technology, internal auditors can enhance risk identification, streamline audit planning, and optimize resource allocation. Additionally, the index promotes improved communication and reporting to stakeholders and allows for continuous monitoring and real-time auditing capabilities. Through a thorough analysis of methodologies, best practices, and case studies, the paper offers actionable insights for organizations eager to strengthen their internal audit functions. It also tackles common challenges in developing an IADI and suggests strategies to overcome potential hurdles. The discussion further explores emerging trends and innovations, such as artificial intelligence and predictive analytics, emphasizing their capacity to revolutionize internal audit practices. Ultimately, this paper highlights the critical need for a data-driven approach in internal audits to navigate the complexities of today's business landscapes effectively.